Key Factors Affecting Business Sustainability of MSMEs in Indonesia: The Role of Intellectual Capital, Social Innovation, and Social Bricolage - Iskandar, Yusuf; Ardhiyansyah, Andri; Pahrijal, Rival (The Eastasouth Management and Business, 2024)
This study examines intellectual capital, social innovation, and social bricolage as three factors that may affect the sustainable business practices of MSMEs in Indonesia. Purposive sampling technique was used in this study and produced 376 pieces of data. With SEM PLS data analysis was carried out on all samples and yielded results that intellectual capital, social innovation, and social bricolage had a significant effect on the business sustainability of MSMEs in Indonesia. MSMEs should actively seek opportunities for collaboration and knowledge sharing with other organizations, industry associations, and academic institutions. This can help them access new ideas, expertise, and resources that can contribute to their business sustainability.